ANALISIS KINERJA LAPORAN KEUANGAN DAN PERHITUNGAN PAJAK PENGHASILAN PASAL 21 PADA PT MULTI SUKSES - Rian Agustini; Ahmad Tomu (JURNAL ULET (Utility, Earning and Tax), 2018)
This study aims to determine the performance of financial statements and income tax at PT Multi Sukses.This research method uses descriptive research methods. The collection is done by: (1) Conducting Observation which is a direct observation of the activity of calculating Article 21 income tax on PT Multi Sukses. (2) Conducting interviews that are conducting interviews with people who can be used as resource persons who are considered to have adequate knowledge of the problem under study. This interview can be done with the leadership or employees of PT Multi Sukses company. (3) Literature techniques, namely by looking for data on monthly reports in the company.To find out the difference in the performance of PT Multi Sukses's financial statements, liquidity, leverage and profitability ratios are used. Article 21 income tax is calculated by taking into account the tax rate.The results of the analysis show that PT Multi Sukses's financial performance is in a good level of liquidity. surveyed from the leverage ratio from 2014 to 2015 has decreased, PT Multi Sukses has a good leverage ratio. The smaller the ratio level, the safer. Profitability ratios from 2014 to 2015 have increased. PT Multi Sukses is obliged to pay off the lack of tax payments payable under the law before the Annual Income Tax notification letter is submitted and no later than the deadline for submitting annual notification letters.